2013
DOI: 10.1097/hjh.0b013e328362bbd6
|View full text |Cite
|
Sign up to set email alerts
|

Systolic left ventricular function according to left ventricular concentricity and dilatation in hypertensive patients

Abstract: The new four-group classification of LVH identifies dilated subgroups with reduced left ventricular function among patients currently classified with eccentric or concentric LVH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 41 publications
2
16
0
1
Order By: Relevance
“…Compared with the nondilated groups, the dilated groups in the present study had increased cardiac output and stroke volume and, therefore, increased wall stress, as well as more segmental wall motion abnormalities. 20 Supporting this finding, although the numbers were small, cardiovascular mortality seemed to be higher in the dilated versus nondilated groups in the present study.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…Compared with the nondilated groups, the dilated groups in the present study had increased cardiac output and stroke volume and, therefore, increased wall stress, as well as more segmental wall motion abnormalities. 20 Supporting this finding, although the numbers were small, cardiovascular mortality seemed to be higher in the dilated versus nondilated groups in the present study.…”
Section: Discussionsupporting
confidence: 80%
“…A recent analysis using this model in highrisk hypertensive patients enrolled in the LIFE trial revealed significant differences in hemodynamic and renal function patterns among the 4 groups despite lack of significant differences among the groups in baseline blood pressure. 20 There is consistency in the literature linking concentric LVH with poor outcome, 1,30 whereas published studies report conflicting results on the association between eccentric LVH and outcome. 2,19,29 In the present study, the new 4-group classification system of LVH failed to detect associations of nondilated eccentric LVH with all-cause or cardiovascular mortality or overall cardiovascular events.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Dilated LV geometries as identified by this new classification have been shown to be strongly related to the presence of microalbuminuria in a large group of hypertensive patients. 21 Furthermore, when this classification was applied to high-risk hypertensive patients enrolled in the LIFE trial, it revealed significant differences in haemodynamic patterns and LV function 22 and enhanced prediction of cardiovascular prognosis. 10 In fact, both dilated and Metabolic syndrome and left ventricular dilatation E Ratto et al concentric patterns were found to be associated with increased incidence of cardiovascular events, whereas the eccentric nondilated group was not.…”
Section: Discussionmentioning
confidence: 98%
“…Recently, a new four-group left ventricular hypertrophy classification based on both left ventricular dilatation and concentricity was proposed [5]. When this classification is applied to patients with hypertension, that is the most common cause of left ventricular hypertrophy, the presence of left ventricular chamber dilatation allows us to identify various clinical phenotypes having specific haemodynamic patterns, left ventricular function [6] and cardiovascular prognosis [7].…”
Section: Introductionmentioning
confidence: 99%